圆筒内表面加工方法 (2016)
种圆筒内表面加工方法。在已在圆筒内表面上形成粗糙表面之后，热喷镀膜被附着到基体构件的圆筒内表面上。锥形面构造成使轴向端部的内径比缸孔内表面的其它部分的内径大。在形成锥形面之后，搪磨热喷镀膜。在圆筒内表面形成镀层之后对热喷镀膜进行搪磨或其它机械精加工的情况下，该方法防止圆筒内表面端部的热喷镀膜剥落。 A thermally sprayed coating is deposited onto a cylindrical internal surface of a base member after a rough surface has been formed on the cylindrical internal surface. The tapered surface is configured such that the internal diameter of the axial end portion is larger than the internal diameter of the remaining portions of the cylinder bore internal surface. After the tapered surface is formed, the thermally sprayed coating is honed. This method prevents exfoliation of a thermally sprayed coating at an end portion of a cylindrical internal surface in a situation where honing or another mechanical finishing process is applied to the thermally sprayed coating after the coating is formed on the cylindrical internal surface.